The microbial peace-signal hypothesis: distributed immune “peace hubs” across the human body - Han, Cliff Shunsheng (Frontiers in Immunology, 2026)
The human immune system depends on microbial partners to maintain restraint. Short-chain fatty acids (SCFAs), produced by anaerobic fermenters in the gut, mouth, and skin, act as biochemical “peace signals” that calm immune activation and promote tolerance. In this hypothesis, “peace signals” refer primarily to microbially derived SCFAs; additional microbial metabolites are discussed as possible but more speculative contributors to immune restraint. This Microbial Peace-Signal Hypothesis proposes that immune homeostasis is not a static legacy of early-life microbial exposure, but a continuous partnership with these commensal fermenters. Modern lifestyle factors—including excessive hygiene, antibiotics, and low-fiber diets—have collapsed the ecological niches that support SCFA-producing guilds. Their loss silences microbial peace signals and drives the epidemic rise of allergies and autoimmune diseases. Unlike the “hygiene” or “old friends” hypotheses, this framework positions microbial peacekeeping as a lifelong metabolic function. It predicts that restoring SCFA producers across all major surfaces—gut, oral, and skin—will reduce immune overactivation systemically. This hypothesis unites clinical, ecological, and evolutionary evidence, suggesting that maintaining distributed SCFA-producing microbiomes is the foundation of long-term immune peace.